Gambaran Pengetahuan Dan Sikap Ibu Tentang Kejadian Diare Pada Balita Di Kecamatan Pontianak Utara - Cantika, Cici (Universitas Tanjungpura, 2023)
Diarrhoeal disease is the second leading cause of death in children under five years old. Each year diarrhea kills about 525,000 in toddlers. Globally, there are nearly 1.7 billion cases of diarrheal diseases in children each year. Diarrhea can be avoided if a mother has good knowledge and attitude about diarrhea. The knowledge and attitudes possessed by mothers will later influence behavior when preventing and handling diarrheal diseases in toddlers. This study used quantitative research using quantitative descriptive research methods with a Cross Sectional approach. The subjects of this study were mothers who had toddlers in the working area of the North Pontianak Equatorial Health Center. The results showed that of the 94 respondents of mothers with good knowledge was the category most owned by mothers, amounting to 73 people (78%), the knowledge category was quite 21 people (22%). Then mothers who have a good attitude are the most common category with 88 people (94%), the attitude category is enough to number 6 people (6%).